2019
DOI: 10.1128/mbio.01428-19
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Mediated Pyrin Oligomerization Nucleates Antiviral IFI16 Sensing of Herpesvirus DNA

Abstract: The formation of multimerized protein assemblies has emerged as a core component of immune signal amplification, yet the biochemical basis of this phenomenon remains unclear for many mammalian proteins within host defense pathways. The interferon-inducible protein 16 (IFI16) is a viral DNA sensor that oligomerizes upon binding to nuclear viral DNA and induces downstream antiviral responses. Here, we identify the pyrin domain (PYD) residues that mediate IFI16 oligomerization in a charge-dependent manner. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…However, it was also shown that a fraction of cGAS can locate to the nucleus in primary cells, and that cGAS stabilizes IFI16, and thereby promotes, the sensing of HSV-1 [17]. Moreover, several reports suggest that IFI16 could be directly associated with herpesviral DNA in the nucleus [16,18], most likely mediated through oligomerization via its Pyrin domains [19]. As a consequence of oligomerization, IFI16 can form filamentous structures in viral replication compartments after infection with an ICP0-deficient HSV-1, and it is thought that these structures restrict viral gene expression [20].…”
Section: Dna Sensor Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was also shown that a fraction of cGAS can locate to the nucleus in primary cells, and that cGAS stabilizes IFI16, and thereby promotes, the sensing of HSV-1 [17]. Moreover, several reports suggest that IFI16 could be directly associated with herpesviral DNA in the nucleus [16,18], most likely mediated through oligomerization via its Pyrin domains [19]. As a consequence of oligomerization, IFI16 can form filamentous structures in viral replication compartments after infection with an ICP0-deficient HSV-1, and it is thought that these structures restrict viral gene expression [20].…”
Section: Dna Sensor Proteinsmentioning
confidence: 99%
“…More studies are needed to identify the cellular enzymes that mediate respective histone modifications and whether they are directly recruited by IFI16 to viral genomes. IFI16 is rapidly recruited to incoming viral genomes [18,22], and several studies show IFI16 oligomerization in the proximity of viral genomes at later time points using confocal and live cell microscopy [19,31]. Intriguingly, there was no evidence for the association of viral DNA with IFI16 or PML-NBs after nuclear entry of adenoviruses [32,33].…”
Section: Dna Sensor Proteinsmentioning
confidence: 99%
“…Furthermore, additional HSV-1 products have been demonstrated to target down-stream signaling molecules in the cGAS STING pathway. For instance, Upton et al, 2012;Pham et al, 2013;Kuriakose et al, 2016;Lin et al, 2016;Maelfait et al, 2017;Guo et al, 2018;Daniels et al, 2019;Ingram et al, 2019;Rothan et al, 2019;Yang et al, Gao D. et al, 2013;Li et al, 2013;Sun et al, 2013;Herzner et al, 2015;Ma F. et al, 2015;Bode et al, 2016;Vermeire et al, Unterholzner et al, 2010;Conrady et al, 2012;Orzalli et al, 2012;Ansari et al, 2013;Cuchet-Lourenco et al, 2013;Jakobsen et al, 2013;Dell'Oste et al, 2014;Diner et al, 2015;Dutta et al, 2015;Iqbal et al, 2016;Pisano et al, 2017;Lum et al, 2019;Roy et al, 2019;Yang et al, Fernandes-Alnemri et al, 2009;Hornung et al, 2009;Rathinam et al, 2010;Reinholz et al, 2013;Sagulenko et al, 2013;Ekchariyawat et al, 2015;Corrales et al, 2016;Gray et al, 2016;…”
Section: Cgas/stingmentioning
confidence: 99%
“…While there is conflicting evidence for the role of IFI16 in IFN-β responses to foreign DNA challenge, multiple lines of investigation indicate that this DNA sensor contributes to IFN-β and ISG expression following viral infection (Orzalli et al, 2012 ; Jakobsen et al, 2013 ; Ansari et al, 2015 ; Diner et al, 2015 ; Ma F. et al, 2015 ; Li et al, 2016 ; Zhang D. et al, 2016 ; Jønsson et al, 2017 ; Lum et al, 2019 ; Yang et al, 2020 ). For example, nuclear IRF3 translocation and subsequent IFN production in HSV-1 infected corneal epithelial cells has been shown to be dependent, at least in part, on p204 expression (Conrady et al, 2012 ), while TBK-1 phosphorylation and subsequent IFN-β expression by HSV-1 infected HFFs was found to require IFI16 and STING (Orzalli et al, 2012 ).…”
Section: Ifi16mentioning
confidence: 99%
“…In the past few years, accumulating evidence has demonstrated that nuclear DNA sensors, such as IFN-γ-inducible protein 16 (IFI16), heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNPA2B1), and nuclear cGAS, also exert critical roles in initiating host antiviral immunity ( 10 ). However, compared to the wealth of knowledge about cytosolic DNA sensors and the other PRRs, studies for the roles and underlying mechanisms of nuclear DNA sensors are only just emerging ( 11 13 ). Recent evidence indicates that nuclear DNA sensors are also involved in tumor development beyond pathogenic DNA recognition.…”
Section: Introductionmentioning
confidence: 99%